PENGARUH PERENCANAAN PAJAK DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdul Muslim; Ahmad Junaidi (JURNAL LENTERA BISNIS, 2020)
This study aims to measure tax planning and profitability on firm value in mining companies listed on the Indonesia Stock Exchange for the period 2014-2018. Firm value, tax planning, and profitability use the Q ratio (Tobins Q), Effective Tax Rate (ETR), and Return on Equity (ROE). The research sample consisted of 36 data and the method of analysis used multiple linear regression analysis. The test results show that tax planning has an effect but not significantly on firm value and profitability has a significant effect on firm value.Keywords: Tax planning, profitability, company value